A Model of Communicative Teaching and Learning of English Vocabulary Through Interactive Actin vities - Sahraini Sahraini (Universitas Cokroaminoto Palopo, 2015)
Teaching English vocabulary is very important, and it is more than just presenting and introducing new vocabulary to the students. Knowing words is not only memorizing them, but the students need to understand the meaning of the word in context and how the words are used. This can be achieved through correct vocabulary instruction which should involve vocabulary selection, word knowledge, and techniques. The needs of prospective teachers in mastering English both spoken and written, and the ability to teach using English as the language of instruction in the teaching and learning process in the classroom is very important. They also need the skills to teach English effectively and enjoyable to make the students have confident to use English communicatively. Deciding an interesting method for students is also an English teachers’ job to do. In this paper the writer tries to design a model of teaching and learning of English vocabulary through interactive activities. By using a lot of interactive activities, hopefully the students are able to practice to communicate by using English in oral and written.